The Degree of Observing the Values of Love and Tolerance in the Social Studies Textbooks of the Second Intermediate Class from the Perspective of Teachers and Supervisors - Abdullah Al-Khazraji, salam Muhammad (Journal of Tikrit University for Humanities, 2020)
The study aimed to identify the degree of observing the values of love and tolerance in the social studies textbooks of the second class from the perspective of teachers and supervisors and identifying the areas of the values of love and tolerance included in the social studies textbooks of the second intermediate class in Iraq. The study adopted the descriptive approach and the study sample consisted of all the teachers of the second class who taught the textbooks of social studies in the directorate of education of Salah Al-Din for the academic year 2018-2019. The sample consisted of (58) male and female teachers and supervisors. The research concluded that there was a medium degree for observing the values of love and tolerance by the social studies textbooks of the second class from the perspective of teachers and supervisors and that there are no statistical differences at sig. (α = 0.05) for the degree of observing the values of love and tolerance in the social studies textbooks of the second grade from the perspective of teachers and supervisors according to the variables of gender, job, experience, and scientific qualification. The research recommended focusing on the values of love and tolerance in all their fields through using the Holy Qur'an and the Sunna in the social studies' textbooks in Iraq.